Cochrane Review: Prophylactic phototherapy for preventing jaundice in preterm or low birth weight infants. Issue 1 (9th January 2013) - Okwundu, Charles I; Okoromah, Christy AN; Shah, Prakeshkumar S
Abstract Background Low birth weight and premature infants are at major risk for exaggerated hyperbilirubinaemia and jaundice that can lead to bilirubin encephalopathy. Phototherapy is the most common treatment for neonatal hyperbilirubinaemia and could be most effective in preventing the sequelae of hyperbilirubinaemia if initiated prophylactically. Objectives To evaluate the efficacy and safety of prophylactic phototherapy for preterm (< 37 weeks gestational age) or low birth weight infants (birth weight < 2500 g). Search methods We searched the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library, Issue 3) on 31 March 2011, MEDLINE (1950 to 31 March 2011), EMBASE (1980 to 31 March 2011) and CINAHL (1982 to 31 March 2011). Selection criteria Randomised controlled trials or quasi‐randomised controlled studies evaluating the effects of prophylactic phototherapy for preterm or low birth weight infants. Data collection and analysis Two authors independently obtained data from published articles. We performed fixed‐effect meta‐analysis for the outcomes: rate of exchange transfusion, cerebral palsy or other neurodevelopmental impairment, peak serum bilirubin level and all‐cause mortality. Main results Nine studies of 3449 participants were included. The rate of exchange transfusion was reduced in one study with liberal transfusion criteria (risk ratio (RR) 0.20; 95% confidence interval (CI) 0.13 to 0.31) but not in the other two more recent studies with stringent criteria (typical RR 0.66; 95% CI 0.19 to 2.28). There was no statistically significant difference in the rate of cerebral palsy (typical RR 0.96; 95% CI 0.50 to 1.85; two studies, 756 participants). However, one large study that reported on neurodevelopmental impairment (a composite outcome including cerebral palsy) found a slightly lower rate of neurodevelopmental impairment with prophylactic phototherapy (RR 0.85; 95% CI 0.74 to 0.99; 1804 participants). The prophylactic phototherapy group had lower peak bilirubin levels (mean difference (MD) ‐2.73; 95% CI ‐2.89 to ‐2.57; six studies, 2319 participants) and had fewer neonates with peak unconjugated serum bilirubin levels > 10 mg/dl (typical RR 0.27; 95% CI 0.22 to 0.33; three studies, 1090 participants) or peak unconjugated serum bilirubin levels > 15 mg/dl (typical RR 0.13; 95% CI 0.07 to 0.23; four studies, 1116 participants). There was no statistically significant difference in the rate of all‐cause mortality between the two groups (typical RR 1.08; 95% CI 0.93 to 1.26; four studies, 3044 participants). Authors' conclusions Prophylactic phototherapy helps to maintain a lower serum bilirubin concentration and may have an effect on the rate of exchange transfusion and the risk of neurodevelopmental impairment. However, further well‐designed studies are needed to determine the efficacy and safety of prophylactic phototherapy on long‐term outcomes including neurodevelopmental outcomes. Plain Language Summary Prophylactic phototherapy for preventing jaundice in preterm very low birth weight infants Preterm (< 37 weeks gestational age) or low birth weight (LBW; birth weight < 2500 g) infants have a greater risk of developing jaundice compared to term or normal birth weight infant. This can be concerning because jaundice (caused by high levels of serum unconjugated bilirubin) could lead to permanent brain damage and/or death. In this review we evaluated the efficacy and safety of prophylactic phototherapy in preventing jaundice in preterm or LBW infants. A total of nine clinical trials representing 3449 infants were included. The findings suggest that phototherapy initiated soon after birth (within 36 hours) for preterm or low birth weight infants may prevent the serum bilirubin from reaching a level that would require exchange transfusion and may reduce the risk of impairment of brain and central nervous system development. However, further well‐designed studies are needed to evaluate the effects of prophylactic phototherapy on brain and central nervous system development and other long‐term outcomes.